Distribution patterns of Triatominae (Hemiptera: Reduviidae) in the Americas: an analysis based on networks and endemicity. (11th February 2022) - Ferrari, Augusto; Janisch Alvares, Diego; Buratto, Patrícia Maria; Ribeiro Barão, Kim
Abstract: Triatominae, commonly known as kissing bugs, are a group of approximately 150 species of hematophagous reduviids, some of which are vectors of Trypanosoma cruzi, the etiological agent of the Chagas disease. Distributional patterns of triatomines have been studied based on macroecological and historical biogeographic approaches, but the definition of distributional patterns and areas of endemism are yet to be defined based on objective criteria. We used two methods to identify biogeographic units in the Triatominae: the endemicity analysis based on an optimality criterion (NDM/VNDM software) and a network approach aimed to simplify and highlight the underlying structure in species distributions (Infomap Bioregions). Information on species distributions was obtained from a data paper, comprising 21 815 records for 135 triatomine species occurring in the Americas. The resulting areas of each method were clustered using a meta consensus criterion based on dissimilarities and interpreted as recurrent areas. The NDM areas show a nested structure, presenting greater restrictions to the inclusion of species in a given area, requiring broad sympatry. In contrast, bioregions emphasize spatial patterns with better‐delimited areas and species occurrences do not need to be highly congruent. When areas were clustered based on their species composition two clear patterns arose from both methods: (i) areas within the southern Amazon and southeast South America, especially in the Chacoan subregion, formed a cluster, and (ii) areas north of the Amazon, Pacific, Mesoamerica, Mexican transition zone and Nearctic formed another cluster. Moreover, within each of these two clusters, there was a latitudinal gradient of the areas in the Americas showing spatial similarity between the areas found in both methods. Results of both methods show well‐bound areas separating the triatomine fauna in the Brazilian subregions, resulting in the recognition of areas corresponding to the biomes Chaco, Pampa, Cerrado, and Caatinga, and, to a lesser extent, the Atlantic Forest.